下顎骨辺縁切除（口内法）における歯科用切除バーの有用性 - Onitsuka Tetsuro; Iida Yoshiyuki; Asano Rie (Stomato-pharyngology, 2009)
Marginal mandibulectomy preserving intact teeth or dental roots in lateral lesion (premolar-molar) when many normal teeth remain is a significant challenge, because the saw direction and angle is limited by the lower lip and teeth. In such cases, we use a dental excision bar (Osada Denki Kogyo Corporation) having a small head and blade resembling a drill that both penetrates and cuts the bone with the lateral face of the blade moving parallel to its major axis. The device operates omnidirectionally, making it useful for intentional, accurate marginal mandibulectomy in the small intraoral space between the buccal mucous membrane and the gingiva. 下歯肉癌に対する口内法による下顎骨辺縁切除の際, 残存歯があった場合, 側方の小臼歯～大臼歯付近では, 刃の入る方向や角度が下口唇, 残存歯に制限される. このため健常歯やその歯根, 下顎管などを保存しつつ, 計画どおりに骨切りを行うことは容易ではない. そのような症例に当科では歯科用の切除バーを使用している. このバーの刃はドリル状で, ヘッドが小さく, 骨を穿通させることはもちろん, 長軸に平行に動かすことによりブレードの側方での骨切断も可能で, 切除方向の自由度に優れる. そのため, 頬粘膜, 歯肉間のような狭い口腔内での自在な骨切除に有用である.